Дискурсивний інструментарій аналізу англомовної реклами - Мартинюк, А.П. (Центр наукових досліджень та викладання іноземних мов НАН України, 2009)
The article presents discursive tools of analysis of English advertising. It defines advertising discourse as impelling in accordance with the communicative intention of its global strategy. The paper establishes the main types of the communicative impelling on the basis of advertising discourse local strategies – rational and emotional argumentation and suggestion – and introduces lingual-cognitive means of the strategies realization.